Practical submodule capacitor sizing for modular multilevel converter considering grid faults - Yin, Zhijian (2021)
Submodule (SM) capacitors are key elements in the modular multilevel converter (MMC), the design of which influences the entire system performance. In practical cases, SM capacitor sizing must consider the abnormal system operation (e.g., grid faults). In order to find a clear design boundary for SM capacitors, a practical capacitor sizing method is presented for the first time in this paper, considering the grid-fault-ride-through operation of the MMC, impact of MMC control system, and aging mechanism of capacitors. The SM capacitor rated voltage, capacitance, ESR, thermal resistance, and lifetime can be decided to ensure reliable operations of the MMC during grid faults. The effectiveness of the proposed method has been verified through experimental tests on a down-scale MMC system.